Supportive Care Needs and Patient Preferences Among Hemodialysis Patients with Chronic Kidney Disease: A Scoping Review of Evidence for Patient-Centered Kidney Supportive Care - Handayani, Meyla Sari; Ibrahim, Kusman; Rahayuwati, Laili; Fauzan, Naufal (Journal of Applied Nursing and Health, 2026)
Background: Patients with Chronic Kidney Disease (CKD) undergoing maintenance Hemodialysis (HD) face physical, psychological, social, and spiritual challenges that reduce quality of life. This scoping review mapped and synthesised evidence on supportive care needs and patient preferences to inform the development of holistic, person-centred, and culturally responsive Kidney Supportive Care (KSC) models for adults receiving maintenance HD. Methods: This scoping review followed the PRISMA-ScR guidelines and the Arksey and O'Malley methodological framework, guided by the Population–Concept–Context (PCC) approach. Literature searches were conducted on May 25, 2026, across PubMed, Scopus, ScienceDirect, and EBSCOhost. Eligible studies included English- and Indonesian-language publications from 2021–2026 involving adults with CKD receiving maintenance HD. Qualitative, quantitative, and mixed-methods studies, as well as systematic reviews, were included. Study selection, data charting, thematic synthesis, and methodological quality appraisal were conducted using predefined criteria and Joanna Briggs Institute (JBI) critical appraisal tools. Results: Twelve studies met the inclusion criteria. Four overarching themes were identified: (1) multidimensional supportive care needs, including physical symptom management, psychological support, social and financial assistance, spiritual care, and informational needs; (2) patient preferences for patient-centered care, emphasizing effective communication, shared decision-making, family involvement, and respect for spiritual values; (3) barriers to KSC implementation, including workforce limitations, inadequate psychosocial resources, financial burdens, insufficient professional training, and organizational constraints; and (4) strategies to strengthen KSC through interdisciplinary collaboration, Patient-Reported Outcome Measures (PROMs), family engagement, and integrated palliative care approaches. The review also identified evidence gaps regarding culturally adapted supportive care models, caregiver-support interventions, and implementation strategies in resource-limited settings. Conclusion: Cultural beliefs are crucial in shaping treatment choices for ENT conditions. Public awareness campaigns by the Ministry of Health and local health authorities are recommended to educate communities on the benefits and risks of traditional medicine while promoting evidence-based healthcare practices.